Emerging Technologies in English Writing: AI Chatbots’ Benefits, Challenges, and Implications - Romadhon, Romadhon; Yuliyanti, Novy (urn:multiple://2988-7828multiple.v3i14)
The integration of artificial intelligence (AI) chatbots in English writing education has emerged as a transformative approach, offering innovative solutions to traditional challenges. This study explores the pedagogical benefits, challenges, and implications of using AI chatbots in teaching English writing, employing a library research approach to analyze existing literature. The findings highlight the significant advantages of AI chatbots, including personalized, real-time feedback, enhanced learner engagement, and scalability in addressing diverse student needs. However, challenges such as limited contextual understanding, ethical concerns about data privacy, and the risk of over-reliance on technology are identified as critical issues. The study underscores the importance of blending AI chatbots with human instruction to achieve balanced and comprehensive learning outcomes. Recommendations include equipping educators with digital literacy skills, addressing ethical and accessibility concerns, and fostering collaboration between technology developers and educators. The study concludes that AI chatbots, when thoughtfully integrated, have the potential to enhance English writing education, fostering inclusivity and preparing students for real-world communication demands